1961
DOI: 10.1161/01.cir.23.6.847
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol and Atherosclerosis in Man

Abstract: Two hundred cases were selected from medicolegal autopsies for a study of the relationship of serum cholesterol to the amount and severity of atherosclerosis in the aorta and the coronary and cerebral arteries. A preliminary study of cholesterol before and after death in 20 cases showed a close parallel between the two when the sample of blood was taken within 16 hours of death. The mean serum total cholesterol showed a tendency to rise from 122 mg. per cent ±16 in the first decade to 176 mg. per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
4

Year Published

1962
1962
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 14 publications
1
4
0
4
Order By: Relevance
“…Already in 1936, Landé and Sperry falsified the first prediction. In a study of a large number of healthy people who had died violently, they found that on average those with low cholesterol were just as atherosclerotic as those with high cholesterol [56], and their result has been confirmed by others [57][58][59][60][61] been present between blood cholesterol and degree of atherosclerosis in studies of selected patient groups. As these groups mainly included patients with cardiovascular diseases, individuals with FH must have been much more frequent than in unselected cohorts.…”
Section: The Effect Of High Cholesterol On Atherosclerosismentioning
confidence: 79%
“…Already in 1936, Landé and Sperry falsified the first prediction. In a study of a large number of healthy people who had died violently, they found that on average those with low cholesterol were just as atherosclerotic as those with high cholesterol [56], and their result has been confirmed by others [57][58][59][60][61] been present between blood cholesterol and degree of atherosclerosis in studies of selected patient groups. As these groups mainly included patients with cardiovascular diseases, individuals with FH must have been much more frequent than in unselected cohorts.…”
Section: The Effect Of High Cholesterol On Atherosclerosismentioning
confidence: 79%
“…On the other hand, there was no obvious correlation between the total serum cholesterol and the severity of atherosclerosis of the aorta or cerebral artery in accord with our previous study13) and reports by Paterson and associates6),7) and Mathur and associates. 8) A close correlation of the blood pressure to the severity of atherosclerosis in the aorta, the coronary or cerebral arteries have been pointed out by many investigators, 9)-15),18)-26),23)-26) although there are some contradictory reports.22),27) However, the studies on the blood pressure are frequently not without objections, especially when only one reading of the blood pressure is available. In order to exclude the influence of transient fluctuations of the blood pressure, only the cases with long follow-up of the blood pressure were included in the present study, and the average of the annual blood pressure was calculated.…”
Section: Discussionmentioning
confidence: 98%
“…Ursächliche Zusammenhänge zwischen Cholesterinspiegel und Herzinfarkt können durch die vorliegenden Studien bisher nicht eindeutig belegt werden. In verschiedenen Untersuchungen post mortem konnten keine Zusammenhänge zwischen dem Grad der Arteriosklerose und den Cholesterinspiegeln gezeigt werden [7,8,9].…”
unclassified